Cloning, expression and functional characterization of a novel a-humulene synthase, responsible for the formation of sesquiterpene in agarwood originating from Aquilaria malaccensis - Yasotha Sundaraj; Hasdianty Abdullah; Nima Ghahremani Nezhad; Kenneth Francis Rodrigues; Suriana Sabri; Syarul Nataqain Baharum (ResearchGate, 2023)
This study describes the cloning, expression and functional characterization of α-humulene synthase, responsible for the formation of the key aromatic compound α-humulene in agarwood originating from Aquilaria malaccensis. The partial sesquiterpene synthase gene from the transcriptome data of A. malaccensis was utilized for full-length gene isolation via a 30 RACE PCR. The complete gene, denoted as AmDG2, has an open reading frame (ORF) of 1671 bp and encodes for a polypeptide of 556 amino acids. In silico analysis of the protein highlighted several conserved motifs typically found in terpene synthases such as Asp-rich substrate binding (DDxxD), metal-binding residues (NSE/DTE), and cytoplasmic ER retention (RxR) motifs at their respective sites. The AmDG2 was successfully expressed in the E. coli:pET-28a(+) expression vector whereby an expected band of about 64 kDa in size was detected in the SDS-PAGE gel. In vitro enzyme assay using substrate farnesyl pyrophosphate (FPP) revealed that AmDG2 gave rise to two sesquiterpenes: α-humulene (major) and β-caryophyllene (minor), affirming its identity as α-humulene synthase. On the other hand, protein modeling performed using AlphaFold2 suggested that AmDG2 consists entirely of α-helices with short connecting loops and turns. Meanwhile, molecular docking via AutoDock Vina (Version 1.5.7) predicted that Asp307 and Asp311 act as catalytic residues in the α-humulene synthase. To our knowledge, this is the first comprehensive report on the cloning, expression and functional characterization of α-humulene synthase from agarwood originating from A. malaccensis species. These findings reveal a deeper understanding of the structure and functional properties of the α-humulene synthase and could be utilized for metabolic engineering work in the future.